2022
DOI: 10.21203/rs.3.rs-1542198/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma metagenomic next-generation sequencing of microbial cell-free DNA detects pathogens in patients with suspected infected pancreatic necrosis

Abstract: Background: Infected pancreatic necrosis (IPN) is a life-threatening complication of acute pancreatitis (AP). Timely diagnosis of IPN could facilitate appropriate treatment, but there is a lack of reliable non-invasive screening tests. In this study, we aimed to evaluate the diagnostic value of plasma metagenomic next-generation sequencing (mNGS) based on circulating microbial cell-free DNA in patients with suspected IPN.Methods: From October 2020 to October 2021, 44 suspected IPN patients who underwent plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The characteristics of all studies are summarized in Table 1. Five (22.7%) of the included studies were prospective [15,16,18,23,32], and 17 studies were retrospective [17,[19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36]. Nine studies (40.9%) of the studies we included tested only blood specimens for mNGS [16-18, 21, 23, 29, 30, 33], and the remaining study specimens included bronchoalveolar lavage uid (BALF), cerebrospinal uid (CSF), urine, biopsy tissue, pus, sputum and so on [15, 19, 20, 22, 24-28, 31, 32, 34-36].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of all studies are summarized in Table 1. Five (22.7%) of the included studies were prospective [15,16,18,23,32], and 17 studies were retrospective [17,[19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36]. Nine studies (40.9%) of the studies we included tested only blood specimens for mNGS [16-18, 21, 23, 29, 30, 33], and the remaining study specimens included bronchoalveolar lavage uid (BALF), cerebrospinal uid (CSF), urine, biopsy tissue, pus, sputum and so on [15, 19, 20, 22, 24-28, 31, 32, 34-36].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 4 (18.18%) studies of all patients with neutropenia[16, 25, 28, 33] and 5 (22.72%) studies of all patients undergoing HSCT [15,22,24,30,32]. Eleven (50.0%) studies reported the percentage of antibiotics adjusted for mNGS [17,19,20,26,28,29,[31][32][33][34]36], and 4 (18.18%) of these studies further reported effective rates after adjusting for antibiotics [19,28,29,36].…”
Section: Study Characteristicsmentioning
confidence: 99%